The very fairy princess - Andrews, Julie; Davenier, Christine; Hamilton, Emma Walton (New York : Little, Brown, 2010)
Despite her scabby knees and dirty fingernails, Geraldine knows that she is a princess inside and shows it through her behavior at home and in school.
Booklist.
Publisher's Weekly.
School Library Journal.
Booklist, April 2010.
Horn Book, October 2010.
Kirkus Review, April 2010.
Keywords: Conduct of life -- Juvenile fiction; Princesses -- Juvenile fiction; Self-perception -- Juvenile fiction; Conduct of life -- Fiction; Princesses -- Fiction; Self-perception -- Fiction; Conduct of life -- Fiction; Princesses -- Fiction; Self-perception -- Fiction; Picture books for children